Fragile X Syndrome: A rare case report with unusual oral features - Prayas Ray; Arpanna Singh; Jayanta Kumar Dash; Prasanna Kumar Sahoo; Jitendra Kumar Dash (Wolters Kluwer Medknow Publications, 2017)
Fragile X syndrome (FXS) is a rare variant of special health-care need demonstrating delayed developmental milestones and associated with intellectual and emotional disabilities ranging from learning problem to mental retardation. The syndrome is usually not diagnosed until 8-9 years of age since the clinical manifestations of the syndrome are greatly attenuated in childhood. The physical characteristics such as facial features, hyperactivity, attention deficit, autistic behavior, and macroorchidism are quite evident in younger age group. The most typical orofacial characteristics associated with children suffering from FXS are mandibular prominence, ogival, and cleft palate. Till date, very few dental literatures have been reported regarding the association of FXS with orodental anomalies. Here, we report a rare case of 14-year-old boy suffering from FXS with typical orofacial characteristics, multiple supernumerary teeth, and dental caries.